2005
DOI: 10.1002/ejic.200500420
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated Ruthenium Compounds Containing 2‐(2′‐Pyridyl)‐ 4‐methylphenyl and Benzo[h]quinolyl Ligands

Abstract: Transmetalation of Hg(ptpy)2 [Hptpy = 2‐(4‐tolylpyridine) with Cp*Ru(NO)Cl2 (Cp* = η5‐C5Me5)] gave [Cp*Ru(NO)(ptpy)]2[Hg2Cl6] ([1]2·Hg2Cl6) whereas that with [Cp*RuCl2]x gave the dinuclear RuII–RuIV compound [Cp*Ru(μ‐η6:η2‐ptpy)RuCl2Cp*][Hg2Cl6] (2). Treatment of Ru(3‐phenylindenylid‐1‐ene)Cl2(PPh3)2 with Hg(ptpy)2 resulted in coupling of ptpy with the 3‐phenylidenylid‐1‐ene ligand, and the formation of Ru(Ph‐ind‐ptpy)(PPh3)Cl {Ph‐ind‐tpy = 3‐phenyl‐1‐[2‐(4‐toyl)pyridyl]indenyl} (3), in which the chelated [Ph‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
3
16
0
Order By: Relevance
“…It shows a “three‐legged piano stool” geometry, analogous to that found in related half‐sandwich chlororuthenium complexes that contain P and N as donor centres 2123. Ru–P and Ru–Cl bond lengths are comparable to those found for [Ru(Ph‐ind‐ptpy)(PPh 3 )Cl] {Ph‐ptpy‐ind = η 5 ‐ κ N ‐3‐phenyl‐1‐[2‐(2‐pyridyl)‐4‐tolyl]indenyl} 23.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…It shows a “three‐legged piano stool” geometry, analogous to that found in related half‐sandwich chlororuthenium complexes that contain P and N as donor centres 2123. Ru–P and Ru–Cl bond lengths are comparable to those found for [Ru(Ph‐ind‐ptpy)(PPh 3 )Cl] {Ph‐ptpy‐ind = η 5 ‐ κ N ‐3‐phenyl‐1‐[2‐(2‐pyridyl)‐4‐tolyl]indenyl} 23.…”
Section: Resultssupporting
confidence: 53%
“…It shows a “three‐legged piano stool” geometry, analogous to that found in related half‐sandwich chlororuthenium complexes that contain P and N as donor centres 2123. Ru–P and Ru–Cl bond lengths are comparable to those found for [Ru(Ph‐ind‐ptpy)(PPh 3 )Cl] {Ph‐ptpy‐ind = η 5 ‐ κ N ‐3‐phenyl‐1‐[2‐(2‐pyridyl)‐4‐tolyl]indenyl} 23. Regarding this complex, the most distinctive features are shorter Ru–ring centroid distance [1.818(5) vs. 1.849(3) Å], Ru–N bond length [2.111(5) vs. 2.169(3) Å], and a smaller P–Ru–N angle [82.08(14) vs. 95.88(7)°], due to a large extent to the bulkiness of the ligands in [Ru(Ph‐ind‐ptpy)(PPh 3 )Cl] and the P–N connection in 2b .…”
Section: Resultssupporting
confidence: 53%
“…Of particular interest are Pd IV and Pt IV bis(chalcogenolate) complexes, which are involved in metal-catalyzed selective addition of E-E bonds to alkynes [21]. Recently, we reported that reaction of Ir III alkyl complexes with R 2 S 2 led to formation of Ir III bis(thiolate) complexes, possibly via oxidative addition of the S-S bond to Ir III and subsequent C-S bond elimination [22]. Thus, in an attempt to prepare higher valent Cp*Ir chalcogenolate complexes, reactions of 1 with R 2 E 2 (E = S, Se, Te) were attempted.…”
Section: Reaction Of [Cp*ir(ppy)(solv)] + With R 2 Ementioning
confidence: 99%
“…Organomercury(II) derivatives have been used successfully to obtain the desired organometallic compounds of transition metals, as well as main group metals otherwise inaccessible by classical Grignard and/or lithiation reactions (Bonnardel et al, 1996;Gul & Nelson, 1999a,b;Berger et al, 2001Berger et al, , 2003Zhang et al, 2005;Djukic et al, 2006). Although the toxicity of mercury compounds should always be taken into account, there are important advantages, e.g.…”
Section: Chemical Contextmentioning
confidence: 99%